Penerapan Program Jaminan Kesehatan Masyarakat Kota Bandar Lampung Berdasarkan Peraturan Walikota Bandar Lampung Nomor 50 Tahun 2018 - Julia Rahayu; Ratna Nur Fadhilah; Martha Yulisa; Kayla Azzahra (Universitas Mitra Indonesia, 2022)
Abstract Health is an important aspect of human rights as stated in the 1945 Constitution in Article 28 H, stipulating that health is a basic right of every individual and all citizens are entitled to health services, including the poor. The Bandar Lampung City Government in 2018 implemented the Health Insurance Program as regulated in the Bandar Lampung Mayor Regulation Number 50 of 2018 to provide social protection in the health sector.The purpose of this study is to find out how the requirements and procedures for obtaining Regional Health Insurance in Bandar Lampung City are, how to apply the distribution of Regional Health Insurance in Bandar Lampung City, what are the inhibiting and supporting factors for the distribution of Health Insurance in Bandar Lampung City. The research method used in this paper is a normative juridical approach and an empirical juridical approach. Secondary data is data obtained from literature studies, and this approach is supported by three materials, namely primary, secondary and tertiary legal materials.The results of the study are that the requirements and procedures for obtaining Regional Health Insurance in Bandar Lampung City are to bring KTP, KK and SKTM to be verified by the Health Office in order to issue Participant Validity Letters, then the application of Regional Health Insurance distribution in Bandar Lampung City has been running but not maximized, it is proven that more than 50% of patients who seek outpatient and inpatient treatment at the Regional General Hospital in Bandar Lampung City use the Regional Health Insurance, but in its application there are still health services that are not guaranteed by the Bandar Lampung Mayor Regulation Number 50 of 2018, then The inhibiting factor for the distribution of Regional Health Insurance in Bandar Lampung City is the lack of medical facilities used by Health Workers to diagnose diseases, while the supporting factor is the fulfillment of Health Workers who provide health services to the community.Keywords: human rights, health insurance, implementation